Innovative Approach for Interstitial Cystitis: Vaginal Pessaries Loaded Diazepam—A Preliminary Study. (20th January 2013) - Capra, P.; Perugini, P.; Bleve, M.; Pavanetto, P.; Musitelli, G.; Rovereto, B.; Porru, D.
Abstract : Bladder pain is a characteristic disorder of interstitial cystitis. Diazepam is well known for its antispasmodic activity in the treatment of muscular hypertonus. The aim of this work was to develop and characterize vaginal pessaries as an intravaginal delivery system of diazepam for the treatment of interstitial cystitis. In particular, the performance of two types of formulations, with and without beta-glucan, was compared. In particular, the preparation of pessaries, according to the modified Pharmacopeia protocol, the setup of the analytical method to determine diazepam, pH evaluation, dissolution profile, and photostability assay were reported. Results showed that the modified protocol permitted obtaining optimal vaginal pessaries, without air bubbles, with good consistency and handling and with good pH profiles. In order to determine the diazepam amount, calibration curves with good correlation coefficients were obtained, by the spectrophotometric method, using placebo pessaries as matrix with the addition of diazepam standard solution. This method was demonstrated sensible and accurate to determine the amount of drug in batches. Dissolution profiles showed a complete diazepam release just after 15 minutes, even if beta-glucan pessaries released drug more gradually. Finally, a possible drug photodegradation after exacerbated UV-visible exposition was evaluated.